Terms and conditions of differentiation and diversifi cation of the insurance market in Kazakhstan - Beisebayevа M. A. (Journal of Economic Research & Business Administration, 2015)
The article describes the main challenges of the insurance market of Kazakhstan. And the terms and conditions of diversifi cation and differentiation of the insurance market. The factors affecting the insurance market. The factors are divided into groups and given a description of each group. The general problems in the insurance market of Kazakhstan and other CIS countries. We consider the strategy of the insurance market in the case of foreign countries. Preconditions of the insurance market of Kazakhstan. And also proposed a phased and integrated development of insurance business. The features of the insurance pre-market period, and their infl uence on the modern insurance market. Infl uence on the development of the insurance old controls of production and economic processes. The article analyzes the barriers to insurance companies as well as the negative factors of the insurance market, and other items. Considered objective and particularly the expansion and differentiation as the main direction of the acceleration development domestic insurance market.